The Red Fox Y-Chromosome in Comparative Context - Halie M. Rando; William H. Wadlington; Jennifer L. Johnson; Jeremy T. Stutchman; Lyudmila N. Trut; Marta Farré; Anna V. Kukekova (Genes, 2019)
While the number of mammalian genome assemblies has proliferated, Y-chromosome assemblies have lagged behind. This discrepancy is caused by biological features of the Y-chromosome, such as its high repeat content, that present challenges to assembly with short-read, next-generation sequencing technologies. Partial Y-chromosome assemblies have been developed for the cat (Felis catus), dog (Canis lupus familiaris), and grey wolf (Canis lupus lupus), providing the opportunity to examine the red fox (Vulpes vulpes) Y-chromosome in the context of closely related species. Here we present a data-driven approach to identifying Y-chromosome sequence among the scaffolds that comprise the short-read assembled red fox genome. First, scaffolds containing genes found on the Y-chromosomes of cats, dogs, and wolves were identified. Next, analysis of the resequenced genomes of 15 male and 15 female foxes revealed scaffolds containing male-specific k-mers and patterns of inter-sex copy number variation consistent with the heterogametic chromosome. Analyzing variation across these two metrics revealed 171 scaffolds containing 3.37 Mbp of putative Y-chromosome sequence. The gene content of these scaffolds is consistent overall with that of the Y-chromosome in other carnivore species, though the red fox Y-chromosome carries more copies of BCORY2 and UBE1Y than has been reported in related species and fewer copies of SRY than in other canids. The assignment of these scaffolds to the Y-chromosome serves to further characterize the content of the red fox draft genome while providing resources for future analyses of canid Y-chromosome evolution.